The rise of the middle class in Ecuador during the oil boom (2017)
In this paper we analyse the evolution of the middle class in Ecuador during the commodities boom (2005-2015). Using the definition of middle class proposed by López-Calva and Ortiz-Juarez (2014), we document an impressive rise of the middle class, which doubled in this period and peaked at 37.4% of the population in 2015. A factor that has played an important role in this social change is the reduction in inequality although growth is responsible for over three-quarters of the rise of the middle class. Based on an analysis of the macroeconomic and labour conditionsassociated with the evolution of the middle class, we argue that the recent slowdown in growth and reduction in inequality following the end of the commodities boom poses a risk for the size of the middle class. This is a serious challenge for policy makers.